Evaluation of KRAS inhibitor-directed therapies for pancreatic cancer treatment - Long, Szu-Aun; Amparo, Amber M.; Goodhart, Grace; Ahmad, Syed A.; Waters, Andrew M. (Frontiers in Oncology, 2024)
Despite significant advancements in the treatment of other cancers, pancreatic ductal adenocarcinoma (PDAC) remains one of the world's deadliest cancers. More than 90% of PDAC patients harbor a Kirsten rat sarcoma (KRAS) gene mutation. Although the clinical potential of anti-KRAS therapies has long been realized, all initial efforts to target KRAS were unsuccessful. However, with the recent development of a new generation of KRAS-targeting drugs, multiple KRAS-targeted treatment options for patients with PDAC have entered clinical trials. In this review, we provide an overview of current standard of care treatment, describe RAS signaling and the relevance of KRAS mutations, and discuss RAS isoform-and mutation-specific differences. We also evaluate the clinical efficacy and safety of mutation-selective and multi-selective inhibitors, in the context of PDAC. We then provide a comparison of clinically relevant KRAS inhibitors to second-line PDAC treatment options. Finally, we discuss putative resistance mechanisms that may limit the clinical effectiveness of KRAS-targeted therapies and provide a brief overview of promising therapeutic approaches in development that are focused on mitigating these resistance mechanisms.